Effect of Cladding Failure on FCCI Layer and Fission Product Behavior - SONG Wulin, PANG Huimei, CHENG Huanlin, JI Songtao, WANG Huacai (Yuanzineng kexue jishu)
Nuclear fuel rods are the first barrier preventing the release of fission products to the environment in the operation of nuclear power plants. Zirconium alloys are favored for their advantages, such as a low neutron absorption cross-section, excellent mechanical properties, and corrosion resistance, making them commonly used as cladding materials for UO2 fuel in pressurized water reactors (PWRs). During reactor operation, a robust fuel-cladding chemical interaction (FCCI) layer forms upon contact between UO2 fuel and zirconium alloy cladding. Furthermore, UO2 fuel will produce a large number of fission products during operation. The accumulation of fission products can change the chemical environment inside the fuel rods, and may also affect the chemical composition and structural stability of FCCI layer and cladding. Understanding the different FCCI layers and fission product distribution characteristics of intact and damaged fuel rods is crucial for predicting the performance of PWR fuel rods during and after service, and designing spent fuel reprocessing technology. The FCCI layer of an intact fuel rod with a burnup of 45 GW·d/tU and a leak fuel rod with a burnup of 41 GW·d/tU from a commercial PWR was systematically analyzed by shielded electron probe microanalysis (EPMA) technique. The experimental results show that the FCCI layer of the intact fuel rod is composed of ZrO2−x. The FCCI layer of the leak fuel rod presents an obvious stratification phenomenon. The entry of high-temperature steam promotes the formation of a (U, Zr)O2−x layer and a transition layer of U and Zr elements between the ZrO2−x layer and UO2 pellet. The two fuel rods also differ in the distribution of fission product elements. In the intact rod, elements such as Mo, Ru and Pd mainly exist in the pellet and the recoil range of the FCCI layer, while in the leak rod, Mo element is distributed in the whole FCCI layer. The results show that the higher oxygen content and larger temperature gradient caused by cladding failure can significantly promote the outward migration of Mo element from the pellet.